1985
DOI: 10.1111/j.1440-1673.1985.tb01707.x
|View full text |Cite
|
Sign up to set email alerts
|

The Carotid Bruit: Is it a Useful Sign of Vessel Disease? A Clinical and Digital Angiographic Study

Abstract: 203 consecutive patients for Digital subtraction angiography of the cranio‐cervical vessels were also assessed for audible bruits in the neck. The sensitivity of bruit as an indicator of carotid disease is 0.57, with specificity of 0.83. The presence of a bruit is a strong indication for angiography by the simple and safe method of DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…While Pessin et al 9 found bruits to predict underlying atherosclerosis reliably, most clinicians agreed with Murie et al 10 that "although a carotid bruit is often a marker of internal carotid intraluminal turbulence and stenosis, this is by no means always so." Similarly, by digital subtraction angiography Dugdale et al 11 showed the sensitivity of bruits as predictors of stenosis (in either carotid artery) to be 57%, with a specificity of 83%, but these authors still concluded that bruits in the elderly are likely to be related to stenosis. Using posteroanterior films of the cervical spine, Imataka et al 12 reported evidence of carotid calcification in only 43% of patients with bruits, which, while >3 times the rate in patients without bruits, was a relatively low proportion with evidence of atherosclerosis.…”
mentioning
confidence: 99%
“…While Pessin et al 9 found bruits to predict underlying atherosclerosis reliably, most clinicians agreed with Murie et al 10 that "although a carotid bruit is often a marker of internal carotid intraluminal turbulence and stenosis, this is by no means always so." Similarly, by digital subtraction angiography Dugdale et al 11 showed the sensitivity of bruits as predictors of stenosis (in either carotid artery) to be 57%, with a specificity of 83%, but these authors still concluded that bruits in the elderly are likely to be related to stenosis. Using posteroanterior films of the cervical spine, Imataka et al 12 reported evidence of carotid calcification in only 43% of patients with bruits, which, while >3 times the rate in patients without bruits, was a relatively low proportion with evidence of atherosclerosis.…”
mentioning
confidence: 99%